PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERDIFERENSIASI EKSTOVERT DAN INTROVERT BERBASIS PROYEK - Sejati, Mezayu Maura; Jaelani, Anton (Universitas Islam Nusantara, 2024)
In mathematics learning at school, there are not many teaching materials that can support the learning process according to the needs of each student. One solution that can help students learn according to their needs is to use differentiated Student Worksheets (LKPD). The aim of this research is to produce a product in the form of a differentiated LKPD in terms of extrovert and introvert personalities using a project-based learning model on flat-sided building material for junior high school students. This type of research is Research and Development (RnD) with a 4D development model by Thiagarajan, which goes through 4 stages: Definition, Design, Development, and Dissemination. The subjects of this research were students in class VIII H of SMPN 5 Purwokerto. The instruments used are questionnaires to measure validity criteria and response questionnaires. The results of the research show that the differentiation LKPD in terms of extrovert and introvert personalities using a project-based learning model on flat-sided building material for junior high school students has met the very valid criteria with an average score of 3.63. Apart from that, this LKPD also received a very practical category with an average score of 3.13. These results indicate that this development product is suitable for use in the learning process.